Effects of light on a P-channel InGaP/GaAs/InGaAs double heterojunction pseudomorphic modulation-doped field effect transistor - Kim, HJ; Kim, DM; Kim, SH; Lee, JI; Kang, KN; Cho, K (JAPAN J APPLIED PHYSICS, 1998)
We report on the effects of light on a p-channel In0.49Ga0.51P/GaAs/In-0.13 Ga0.87As pseudomorphic modulation-doped field effect transistor (MODFET) with a 1 mu m gate length. The threshold voltage (V-th), Obtained in the saturation region, shows nonlinear behavior with an increase in the incident optical power (P-opt). We obtained threshold voltages ranging from V-tho=1.35 V at P-opt=0 mW to V-th=1.55 V at P-opt=2.15 mW. The photocurrent was -0.37 mA at V-gs=0 V and V-ds=-3.5 V with incident optical power of 2.15 mW. The photocurrent is defined as the difference between the drain current with optical illumination and that without optical input. The absolute value of the photocurrent increases nonlinearly with optical power, We observed that the saturated drain currents had a critical point at the gate-source voltage of 1.4 V. This property is expected to be related to nonlinearly increased channel opening under optical illumination, particularly at high gate-source voltages. The current gain cut-off frequency and the maximum frequency of oscillation were also observed to be improved under optical illumination.